Long-term effects of early postnatal stress on Sertoli cells - Thumfart, Kristina M.; Lazzeri, Samuel; Manuella, Francesca; Mansuy, Isabelle M. (Frontiers in Genetics, 2022)
Sertoli cells are somatic cells in testis essential for spermatogenesis, that support the development, maturation, and differentiation of germ cells. Sertoli cells are metabolically highly active and physiologically regulated by external signals, particularly factors in the blood stream. In disease conditions, circulating pathological signals may affect Sertoli cells and consequentially, alter germ cells and fertility. While the effects of stress on reproductive cells have been well studied, how Sertoli cells respond to stress remains poorly characterized. We used a mouse model of early postnatal stress to assess the effects of stress on Sertoli cells. We developed an improved strategy based on intracellular stainings and obtained enriched preparations of Sertoli cells from exposed males. We show that adult Sertoli cells have impaired electron transport chain (ETC) pathways and that several components of ETC complexes particularly complex I, III, and IV are persistently affected. We identify serum as potential mediator of the effects of stress on Sertoli cells by showing that it can recapitulate similar ETC alterations in primary cells. These results highlight Sertoli cells as cellular targets of stress in early life that can keep a trace of exposure until adulthood.